Blended Learning Model for Writing Courses on Media in Era 4.0 (Model Blended Learning untuk Mata Kuliah Menulis Pada Media di Era 4.0) - Muthia Damaiyanti; Desi Yulastri; Sumira Sumira; Edwar Kemal; Wahyudi Rahmat (Indonesian Language Education and Literature, 2022)
This study aimed to describe the development of a blended learning model in the Writing in Media course in the face of the 4.0 era. This study uses the ADDIE model which is limited to the analysis stage. This study uses the following methods: observation with a tick observation technique, and notes; documentation with document analysis techniques; and survey with a questionnaire technique. Research data in the form of curriculum, SAP, and teaching methods. The results of the study indicate that (1) the curriculum must be revised to meet the knowledge needs of students and stakeholders, (2) the components and features of news must be mastered by students because many stakeholders need skills to work, (3) the application of a mixed learning model of writing for course media improve student skills and grades.Tujuan penelitian ini adalah untuk mendeskripsikan pengembangan model blended learning pada mata kuliah Menulis di Media dalam menghadapi era 4.0. Penelitian ini menggunakan model ADDIE yang dibatasi pada tahap analisis. Penelitian ini menggunakan metode: observasi dengan teknik observasi centang, dan catat; dokumentasi dengan teknik analisis dokumen; dan survei dengan teknik kuesioner. Data penelitian berupa kurikulum, SAP dan metode pengajaran. Hasil penelitian menunjukkan bahwa (1) kurikulum harus direvisi untuk memenuhi kebutuhan pengetahuan mahasiswa dan pemangku kepentingan, (2) komponen dan fitur berita harus dikuasai oleh mahasiswa karena banyak pemangku kepentingan membutuhkan keterampilan untuk bekerja, (3) penerapan model pembelajaran campuran menulis untuk media kursus meningkatkan keterampilan dan nilai mahasiswa.